MODEL MEMBANGUN KEPERCAYAAN PELANGGAN DALAM MENINGKATKAN MINAT BELI ULANG PENGGUNA JASA TRANSPORTASI BUS TRANS SEMARANG KORIDOR I - Abdul Rapid Tesepu (Jurnal Riset Bisnis Indonesia, 2014)
The purpose of this study is to analyze and describe the effect of customer value and the physicalfacilities of the company image and customer confidence in buying interest re-User Services TransportBus Trans Semarang. The population used is the whole customer / service user transport TransSemarang. Samples were taken with nonprobability sampling approach. The Structurall EquationModeling (SEM) with Partial Least Square method (PLS) was used to analyze the data. The resultsof the study are all variables that affect each other significantly affect customer value to customerconfidence, physical fasilitisa significant influence on customer trust, corporate image significantlyaffect the confidence of customers, customer value significant effect on re-buying interest, a significanteffect of physical facilities against buying interest re-, significant effect on corporate image re buyinginterest and significant impact on customer confidence buying interest re.Keywords: Customer Value, Physical Facilities, Corporate Image, Customer Trust, Interests BuyRepeat